Collaboration Between Laboratory, Nursing, and Pharmacy Teams in the Early Detection and Management of Drug-Induced Organ Toxicity - Meshal Moutir A Alenezi; Alanazi, Jawaher Khunaysir W; Ghadah Saud Almansour; Adel Badah Alkuwaykibi; Ahmed Nafea Abdullah Alenazi; Maha Ahmed Bnyan Alshammery; Raghad Mohammed Fahad Alanazi; Fatimah Oudah Fayiz Alruwaili; Ahmed Falah Dabis Alrashdi; Thanyah Saeed Hajis Alruwaili (International Journal of Computational and Experimental Science and Engineering, 2024)
Collaboration between laboratory, nursing, and pharmacy teams plays a pivotal role in the early detection and management of drug-induced organ toxicity, a critical aspect of patient safety and effective healthcare. Laboratories are responsible for conducting various tests to identify biomarkers and physiological changes indicative of organ toxicity, providing essential data that can inform clinical decisions. When nurses are integral to this process, they actively monitor patients for signs of adverse drug reactions and report any changes in their condition. This real-time communication ensures that laboratory findings are swiftly translated into actionable insights, bridging the gap between diagnostic results and patient care. Pharmacy teams further enhance this collaborative approach by offering expertise in pharmacotherapy and medication management. They evaluate patient medication regimens to identify potential drug interactions and contraindications while recommending alternatives when necessary. Through interdisciplinary rounds and discussions, pharmacists, nurses, and laboratory professionals can establish protocols for monitoring patients at risk for organ toxicity, developing a coordinated strategy for both prevention and intervention. By fostering a team-oriented environment, healthcare providers can enhance early detection efforts, optimize treatment strategies, and ultimately improve patient outcomes in the management of drug-induced organ toxicity.